Probabilistic diagnostics with P-graphs - Polgár, Balázs; Selényi, Endre (Acta Cybernetica, 2003)
This paper presents a novel approach for solving the probabilistic diagnosis problem in multiprocessor systems. The main idea of the algorithm is based on the reformulation of the diagnostic procedure as a P-graph model. The same, well-elaborated mathematical paradigm - originally used to model material flow - can be applied in our approach to model information flow. This idea is illustrated by deriving a maximum likelihood diagnostic decision procedure. The diagnostic accuracy of the solution is considered on the basis of simulation measurements, and a method of constructing a general framework for different aspects of a complex problem is demonstrated with the use of P-graph models.